PERAN MEDIASI WORK FAMILY CONFLICT PADA PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI WANITA (STUDI KASUS DI UPK PUSKESMAS ALIANYANG DAN UPK PUSKESMAS PAL TIGA KOTA PONTIANAK) - SEKAR, SEKAR HARUM B1021151015 (Jurnal Manajemen Update, 2019)
ABSTRACTWomen who work have two roles, namely the role in family and the role in job. Both roles, if not balanced, can cause conflict. This study aims to examine and analyze the role of mediation work family conflict on the influence of emotional intelligence on the performance of female employees. Research type used is descriptive research with quantitative approach, which test the hypothesis using descriptive statistical analysis and path analysis. The study sample comprised 54 female employees who are married and have at least one child. The results show that emotional intelligence variables have a negative and significant effect on work family conflict, emotional intelligence have a positive and significant effect on employee performance, while work family conflict has a negative and significant effect on employee performance.Keywords:  work family conflict, emotional intelligence, and employee performance.ReferensiAbassi, M. K., & Nadeem, S. (2017). Relationship of Work Family Conflicts and Emotional Intelligence in Islamic Banks of Lahore. Sci.Int.(Lahore), 29 (6), 1257-1259. Ahmad, A. (2008). Direct and Indirect Effect of Work-Family Conflict on Job Performance. The Journal of International Management Studies, 3 (2), 176-180. Akbar, D. A. (2017). Konflik Peran Ganda Karyawan Wanita dan Stres Kerja. Jurnal Kajian Gender dan Anak, 12 (1), 33-48. Akintayo, D. I. (2010). Influence of Emotional Intelligence On Work-Family Role Conflict Management and Reduction In Withdrawal Intentions of Workers In Private Organizations. International Business & Economics Research Journal, 9 (12), 131-141. Allen, T.D., Herst, D.E.L., Bruck, C.S., & Sutton, M. (2000). Consequences Associated With Work-to Family Conflict: A Review and Agenda for Future Research. Journal of Occupational Health Psychology, 5 (2), 278-308. Anwar, M., & Shahzad, K. (2011). Impact of Work-Life Conflict on Perceived Employee Performance: Evidence from Pakistan. European Journal of Economics Finance and Administrative Science, 31, 82-86. Baltes, B. B., Clark, M. A., & Chakrabarti, M. (2009). Work-Life Balance: The Roles of Work-Family Conflict and Work-Family Facilitation. Research Gate. 201-212. Bangun, W. (2012). Manajemen Sumber Daya Manusia. Jakarta: Erlangga. Bar-On, R. (2010). Emotional Intelligence: an integral part of positive psychology. South African Journal of Psychology, 40 (1), 54-62. Bhaskar, P. (2015). Emotional Intilligence and Job Performance in Service Industry. International Journal of Research in Computer Application & Management, 5 (02), 60-65. Bighami, M. K., Abdi, F., & Aliakbar, M. S. (2013). The Effect of Emotional Intelligence on Work-Family Conflict Among Employees in Manufacturing Environment Using Structural Equation Modelling. Shiraz Journal of System Management, 1 (2), 67-79. Campbell, D. J., Campbell, K. M., & Kennard, D. (1994). The Effects of Family Responsibilities on the Work Commitment and Job Performance of Non-professional Women. Journal of Occupational and Organizational Psychology, 67, 283-296. Choeruddin, A. (2016). The Effect of Emotional Intelligence on Job Performance and Turnover Intention: An Empirical Study. Polish Journal of Management Studies, 14 (1), 51-62. Colombo, L., & Ghislieri, C. (2008). The Work-To-Family Conflict: Theories and Measures. TPM, 15 (1), 35-55. Dhani, P., Sehrawat, A., & Sharma, T. (2016). Relationship between Emotional Intelligence and Job Performance: A Study in India Context. Indian Journal of Science and Technology, 9 (47), 1-12. Dorio, J. M., Bryant, R. H., & Allen, T. D. (2008). Work-Related Outcomes of the Work-Family Interface: Why Organizations Should Care. Handbook of Work-Family Integrations: Research, Theory, and Best Practice. Elsevier, Inc. Fahmi, I. (2014). Perilaku Organisasi Teori, Aplikasi, dan Kasus. Bandung: Alfabeta. Frone, M. R., Russel, M., & Cooper, M. (1992). Antecendents and Outcomes of Work-Family Conflict: Testing a Model of the Work-Family Interface. Journal of Applied Psychology, 77 (1), 65-78. Frone, M. R., Russel, M., & Cooper, M. (1994). Relationship Between Job and Family Satisfaction: Causal and Noncausal Covariation?. Journal of Management, 20 (3), 565-579. Ghozali, I. (2011). Aplikasi Analisis Multivariate dengan Program SPSS. Semarang: Badan Penerbit Universitas Diponegoro. Greenhaus, J. H., & Beutell, N. J. (1985). Source of Conflict Between Work and Family Roles. Academy of Management Review, 10 (1), 76-88. Greenhaus, J.H., & Collins, K. M. (1997). Work and Family Influences on Departure from Public Accounting. Journal of Vocational Behavior, 50 (5), 249-270. Goleman, D. (2017). Emotional Intelligence. Jakarta: PT Gramedia Pustaka Utama. Gunu, U., & Oladepo, R. O. (2014). Impact of Emotional Intelligence on Employees’ Performance and Organizational Commitment: A Case Study of Dongote Flour Mills Workers. University of Mauritius Research Journal, 20, 1-32. Husnul, U., Yuliejatiningsih, Y., Rasiman, R. (2016). Pengaruh Kecerdasan Emosional, Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Dinas Pendidikan Kota Semarang. Jurnal Manajemen Pendidikan, 5 (1), 15-30. Kahn, R. L., Wolfe, D. M., Quinn, R.P., Snoek, J. D., & Rosenthel, R. A. (1964). Organizational Stress: Studies in Role Conflict and Ambiguity. New York: John Wiley and Sons, Inc. Kossek, E. E., & Lee, K. H. (2017). Work-Family Conflict and Work-Life Conflict. Oxford Research Encyclopedia of Business and Management, 1-25. Kuncoro, M. (2013). Metode Riset untuk Bisnis dan Ekonomi. Jakarta: Penerbit Erlangga. Kuncoro, M. (2011). Metode Kuantitatif Teori dan Aplikasi untuk Bisnis dan Ekonomi. Yogyakarta: Unit Penerbit dan Percetakan Sekolah Tinggi Ilmu Manajemen YKPN. Lunenburg, F. C. (2011). Emotional Intelligence on Workplace. International Journal of Management of Management, Business, and Administration, 14, 1-6. Majekodunmi, A. E. (2017). Work-Family-Conflict and Family-Work-Conflict as Correlates of Job Performance Among Working Mothers: Implications for Industrial Social Workers. African Journal of Social Work, 7 (1). 52-62. Malekar, S., & Mohanty, R. P. (2008). Factors Affecting Emotional Intelligence: An Empirical Study for Students of Secondary School and Professional Colleges. International Journal of Management, 5 (1), 23-42. Mangkunegara, A.A. (2011). Manajemen Sumber Daya Manusia dan Perusahaan. Bandung: PT REMAJA ROSDAKARYA. Marretih, A. K. E. (2013). Work Family Conflict Pada Ibu Bekerja (Studi Fenomenologi dalam Perspektif Gender dan Kesehatan Mental). Sosial Budaya, 10 (1), 27-37. Mayer, J. D., Salovey, P., & Caruso, D. R. (2008). Emotional Intelligence: New Ability or Eclectic Traits?. American Psychologist, 63 (6), 503-517. Mayer, J. D., Caruso, D. R., & Salovey, P. (2016). The Ability Model of Emotional Intelligence: Principles and Updates. Emotion Review, 1-11. Michel, J. S., May, A. A. B., & Clark, M. A. (2013). Handbook of work-life integration among professionals. Research Gate. Mishra, P. S., & Mohapatra, A. K. D. (2010). Relevance of Emotional Intelligence for Effective Job Performance: An Empirical Study. VIKALPA, 35 (1), 53-61. Mohamad, M, & Jais, J. (2016). Emotional Intelligence and Job Performance: A Study Among Malaysian Teachers. Procedia Economics and Finance. 35, 674-682. Mubassyir, A. H., & Herachwati, N. (2014). Pengaruh Work-Family Conflict terhadap Kinerja Perawat Wanita dengan Variabel Intervening Komitmen Organisasional di RSUD Bhakti Dharma Husada Surabaya. Jurnal Manajemen Teori dan Terapan, 7 (3), 143-162. Muhidin, S. A., & Abdurahman, M. (2007). Analisis Korelasi, Regresi, dan Jalur dalam Penelitian (Dilengkapi Aplikasi Program SPSS). Bandung: CV Pustaka Setia. Narayan, P. R., & Narashiman, K. (2000). Emotional Intelligence and Work Performance: A Conceptual Study. Journal of Mechanical and Civil Engineering. 62-68. Netemeyer, R. G., Boles, J. S., & McMurrian, R. (1996). Development and Validation of Work-Family Conflict and Family-Work Conflict Scales. Journal of Applied Psychology, 81 (4), 400-410. Netemeyer, R. G., Maxham, J. G., & Pullig C. (2005). Conflicts in the Work-Family Interface: Links to Job Stress, Customer Service Employee Performance, and Customer Purchase Intent. Journal of Marketing, 69, 130-143. Noe, R. A., Hollenbeck, J. R., Barry, G., & Wright, P. M. (2013). Manajemen Sumber Daya Manusia: Mencapai Keunggulan Bersaing. Jakarta: Salemba Empat. Noor, N. M. (2003). Work- and Family-Related Variables, Work-Family Conflict and Women’s Well-Being: Some Observations. Carfax Publishing. 6 (3). 298-319. Ogunleye, A. J., & Osekita, D. A. (2016). Effect of Job Status, Gender, and Employees’ Achievement Motivation Behavior on Work Performance: a Case Study of Selected Local Government Employees in Ekiti State, Nigeria. European Scientific Journal, 12 (26), 235-248. Oyewuni, A. E., Osibanjo, A. O., & Adenji, A. A. (2016). Emotional Intelligence and Academic Performance of Undergraduates: Correlations, Implications, and Interventions. Mediterranean Journal of Social Science, 7 (1), 509-516. Priyatno, D. (2013). Analisis Korelasi, Regresi, dan Multivariate dengan SPSS. Yogyakarta: Penerbit Gava Media. Priyono & Marnis (2014). Manajemen Sumber Daya Manusia. Taman Sidoarjo: Zifatama Publisher. Priyono (2016). Metode Penelitian Kuantitatif. Sidoarjo: Zifatama Publishing. Rexhepi, G., & Berisha, B. (2017). The effects of Emotional Intelligence in Employees Performance. International Journal of Business and Globalisation. Robbins, S. P., & Judge, T. A. (2015). Perilaku Organisasi. Jakarta: Salemba Empat. Salovey, M., & Mayer, J. D. (1989). Emotional Intelligence: Imagination, Cognition, and Personality. Baywood Publishing, 9 (3), 185-211. Sanusi, A. (2011). Metodologi Penelitian Bisnis. Jakarta: Salemba Empat. Sergio, R. P., Ormita, L. G. L., Dongca A. L., & Gonzales, J. O. (2015). Emotional Intelligence, Work/Family Conflict, and Work Values Among Customer Service Representatives: Basis for Organizational Support. Journal of Eastern European and Central Asian Research, 2 (1), 1-9. Setyaningrum, R., Utami, H. N., & Ruhana, I. (2016). Pengaruh Kecerdasan Emosional Terhadap Kinerja (Studi Pada Karyawan PT. Jasa Raharja Cabang Jawa Timur). Jurnal Administrasi Bisnis, 36 (1), 211-220. Shofa, F. A., & Kristina, I. K. (2015). Kecerdasan Emosi dan Konflik Peran Ganda pada Dosen Wanita di Universitas Diponegoro. Jurnal Empati, 4 (4), 150-155. Siegall, M., & Cummings, L. L. (1995). Stress and Organizational Role Conflict. Genetic Social and Psychology Monographs. Siddiqui, M. N. (2013). Impact of Work Life Conflict on Employee Performace. Far East Journal of Psychology and Business, 12 (3), 26-40.Sudaryono, (2018). Metodologi Penelitian. Depok: PT. RajaGrafindo Persada. Sudha, J., & Karthikeyan, P. (2014). Work Life Balance on Women Empolyee: A Literature Review. International Journal of Management Research & Review, 4 (3), 797-804. Sugiyono (2013). Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif dan R&D). Bandung: Alfabeta. Sugiyono (2016). Metode Penelitian Manajemen. Bandung: Alfabeta Sunyoto, D. (2011). Analisis Regresi dan Uji Hipotesis. Jakarta: PT. Buku Seru. Suwatno (2011). MANAJEMEN SDM dalam Organisasi Publik dan Bisnis. Bandung: Penerbit Alfabeta Swarnalatha, B. (2017). The Role of Emotional Intelligence in Reducing Worklife Conflicts. Asia Pasific Journal Research, 1, 25-28.Umar, H. (1998). Riset Sumber Daya Manusia. Jakarta: PT Gramedia Pustaka Utama. Warokka, A., & Febrilia, I. (2015). Work-Family Conflict and Job Performance: Lesson from a Southeast Asian Emerging Market. Journal of Southeast Asian Research, 2015 (2015) 1-14. Wibowo (2016). Manajemen Kinerja. Jakarta: PT Raja Grafindo Persada. Yunita, S. N., & Fauziah, N. (2018). Hubungan antara Kecerdasan Emosional dengan Konflik Peran Ganda pada Ibu yang Bekerja di PT. Rajawali Nusindo dan PT. Phapros Tbk Jakarta. Jurnal Empati, 7 (1), 34-43. Zainal, V. R., Hadad, M. D., & Ramly, M. (2014). Kepemimpinan dan Perilaku Organisasi. Jakarta: RajaGrafindo Persada. Zhang, M., Griffeth, R. W., & Fried, D. D. (2011). Work-family conflict and individual concequences. Journal of Managerial Psychology, 27 (7), 696-713.